TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP INTERAKSI SOSIAL ANAK AUTIS DI SEKOLAH DASAR - MUAZAROH, LULUIL (Jurnal Pendidikan Khusus, 2017)
Abstract: This research is motivated by the obstacles in the ability of social interaction of children with autism, including the communication, attitude, group behavior and social norm. Therefore, the social interaction ability of autistic children need to be optimized through Team Assisted Individualization (TAI). The purpose of this research is to strengthen Team Assisted Individualization (TAI) to social interaction of children with autism in Elementary School. This research uses quantitative approach and pre experimental research type using research design one group pretest-posttest design. Methods of data completion using an observation sheet to collect data of social interaction ability of children with autism before and after treatment. Data analysis using non parametric statistic test wilcoxon. The result of data analysis shows Zh = 2.20> Z table = 1.96 at 5% error level (double-sided test). Based on the results of this study can be concluded that there is a significant outbound learning with Team Assisted Individualization (TAI) on the social interaction of children with autism in Elementary School.   Keywords: TAI, Social interaction